2020
DOI: 10.1002/jia2.25420
|View full text |Cite
|
Sign up to set email alerts
|

Changes in kidney function among men having sex with men starting on demand tenofovir disoproxil fumarate – emtricitabine for HIV pre‐exposure prophylaxis

Abstract: Introduction Daily pre‐exposure prophylaxis (PrEP) with tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) is associated with a small but statistically significant decrease in estimated glomerular filtration rate (eGFR). We assessed the renal safety of on‐demand PrEP with TDF/FTC in HIV‐1 uninfected men. Methods We used data from the randomized double‐blind placebo‐controlled ANRS‐IPERGAY trial and its open‐label extension conducted between February 2012 and June 2016 among HIV‐uninfected MSM starting on‐de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 27 publications
4
20
0
Order By: Relevance
“…This suggests a functional stabilization. The average loss of eGFR over the 48-week follow-up is similar to those found in the Intervention Préventive de l’Exposition aux Risques avec et pour les Gays (ANRS IPERGAY) [ 22 ] and Iniciativa Profilaxis Pre-Exposición Open Label Extension (iPrEx OLE) studies [ 21 ]. Moreover, epidemiological data suggest that significant renal impairment is uncommon in patients with long-term exposure to TDF/FTC [ 20 ].…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…This suggests a functional stabilization. The average loss of eGFR over the 48-week follow-up is similar to those found in the Intervention Préventive de l’Exposition aux Risques avec et pour les Gays (ANRS IPERGAY) [ 22 ] and Iniciativa Profilaxis Pre-Exposición Open Label Extension (iPrEx OLE) studies [ 21 ]. Moreover, epidemiological data suggest that significant renal impairment is uncommon in patients with long-term exposure to TDF/FTC [ 20 ].…”
Section: Discussionsupporting
confidence: 63%
“…Older individuals had a higher frequency of baseline eGFR over 90 mL/min/1.73 m 2 and had significantly greater eGFR losses after the intervention, in agreement with previous reports [ 8 , 20 , 21 ]. We did not observe an association between the degree of eGFR reduction and other traditional risk factors for renal dysfunction, such as arterial hypertension or obesity [ 22 , 23 ]. In contrast to what has been observed in previous studies [ 22 , 23 ], a higher frequency of eGFR reduction was observed amongst individuals who had higher baseline GFR values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 articles reported on 11 different RCTs were included in the metaanalyses. 3,5,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] . Most studies defined kidney-related adverse events as elevations in serum creatinine levels Forest plots showing risks among tenofovir disoproxil fumarate-based oral PrEP users for grade 1 and higher kidney-adverse events (A) and grade 2 and higher kidney-related adverse events (B).…”
Section: Resultsmentioning
confidence: 99%